2018
DOI: 10.1259/bjr.20180041
|View full text |Cite
|
Sign up to set email alerts
|

Retreatment with peptide receptor radionuclide therapy in patients with progressing neuroendocrine tumours: efficacy and prognostic factors for response

Abstract: The majority of studies on PRRT have shown that it is effective as an initial treatment. This study with long-term follow-up demonstrates that PRRT is safe and effective retreatment option in patients that have progressed following initial PRRT course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 17 publications
2
54
0
Order By: Relevance
“…It is described that after the initial 4 cycles of PRRT the majority of patients will present with stable disease, but will eventually show disease progression 5 , 39 . Patients that present with progressive disease after at least a year and that have responded well to the initial PRRT cycles are eligible for additional cycles of PRRT as it has been shown that retreatment is beneficial in terms of PFS and is often well tolerated 32 , 40 . A prerequisite for (re)treatment is the presence of positive lesions by [ 68 Ga]Ga-DOTA-TATE on a positron-emission-tomography (PET) scan, indicating SST 2 positive tumors 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is described that after the initial 4 cycles of PRRT the majority of patients will present with stable disease, but will eventually show disease progression 5 , 39 . Patients that present with progressive disease after at least a year and that have responded well to the initial PRRT cycles are eligible for additional cycles of PRRT as it has been shown that retreatment is beneficial in terms of PFS and is often well tolerated 32 , 40 . A prerequisite for (re)treatment is the presence of positive lesions by [ 68 Ga]Ga-DOTA-TATE on a positron-emission-tomography (PET) scan, indicating SST 2 positive tumors 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients that present with progressive disease after at least a year and that have responded well to the initial PRRT cycles are eligible for additional cycles of PRRT as it has been shown that retreatment is beneficial in terms of PFS and is often well tolerated 32 , 40 . A prerequisite for (re)treatment is the presence of positive lesions by [ 68 Ga]Ga-DOTA-TATE on a positron-emission-tomography (PET) scan, indicating SST 2 positive tumors 40 , 41 . However, information about the SST 2 expression of single tumor cells within these lesions and their uptake of the radioligand before and after treatment is often unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 21 (77.8%) of the 27 men and 9 (52.9%) of the 17 women died, which means that nearly one third of the treated patients were still alive more than 12 y after initial diagnosis of inoperable metastatic disease. Different studies report median overall survival ranging from 22 to 71 mo (4,(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence indicates that the kidneys can tolerate mean absorbed doses above the general dose limit of 23 Gy and that patients can receive more than the standard of 4 fractions of 7.4 GBq (35). Recent studies have also reported the use of retreatment for patients with progressed disease (6,7). If higher renal mean absorbed doses are accepted, higher total activity will be administered and bone marrow toxicity might become the dose-limiting factor.…”
mentioning
confidence: 99%